Sleep Disordered Breathing and Nocturnal Hypoxemia in Young Adults with Sickle Cell Disease - Whitesell, P. L. (Sleep Med, 2016)
Sleep disordered breathing (SDB) is reported in up to 69% of adolescents and children with sickle cell disease (SCD) [1], but data regarding the prevalence of SDB in adults with SCD are limited. To obtain a preliminary assessment of the frequency and degree of sleep-related hypoxemia and potential associations with cardiovascular function in adults with SCD, we performed overnight sleep studies, 6-minute walk tests, echocardiograms, hematologic and chemistry panels, and administered the Pittsburgh Sleep Quality Index (PSQI), fatigue and health related quality of life measurement in 20 young adults with SCD attending a sickle cell clinic for routine care. Sleep apnea, defined as an apnea-hypopnea index (AHI) >5 events/hour, was found in 50% of subjects. Traditional clinical indicators such as obesity, the presence of snoring, and reported sleep complaints did not reliably differentiate these subjects. Subjects with an AHI>5 had higher mean systolic blood pressure (p =.03), evidence of impaired left ventricular diastolic function (i.e. increased mitral valve E/A ratio, p =.05), a trend toward greater reduction in 6 minute walk distances (p =.06), and lower Health-related Quality of Life scores (p <=.01). Three of nine subjects with more severe anemia (total Hb < 9.0) demonstrated nocturnal hypoxemia in the absence of sleep apnea. As prolonged and frequent hypoxemic episodes likely increase risks for vaso-occlusive, cardiovascular, and neurologic complications of SCD, these results suggest that the prevalence and severity of SDB should be investigated further in studies of larger patient populations. If confirmed, these findings could identify opportunities to prevent or reduce nocturnal hypoxia and improve outcomes.